Framing of Differences: Visual Product Frames Reduce Consumer Choice Deferrals - Jia, Yanli; Ouyang, Jun; Dong, John Qi; Jiang, Yuwei (Journal of Marketing, 2025)
Consumer choice deferral contributes to the low conversion rate in online retailing. This article investigates the impact of visual product frames on consumers’ decisions regarding choice deferral. The authors show that using visual frames to separate options in a product assortment increases consumers’ relative use of the by-alternative (vs. by-attribute) approach for option comparisons, which induces greater perception of assortment variety and subsequently decreases choice-deferral rate. Through seven preregistered studies (including an eye-tracking study and a field experiment), the authors obtain convergent empirical evidence for these proposed effects and suggest actionable guidelines for online retailers regarding how to best design their product displays to encourage sales.